Leading school with diverse worldviews: Finnish principals’ perceptions - Lipiäinen, Tuuli (Journal of beliefs and values, 2021)
The purpose of this study was to find out what kind of worldviews Finnish principals identify in their schools and the kind of lived realities of worldviews that are affecting schools from the perspective of school leadership. The issues were considered using a wide worldview framework, which includes religious and non-religious worldviews and focused on the lived realities of worldviews. Seven principals in basic education were interviewed, and the resulting data were analysed using both inductive and deductive content analysis methods. According to the results, diversity and a plurality of worldviews was emphasised in the schools, principals identifying a total of 30 different worldviews including both religious and non-religious worldviews. The lived realities of worldviews were separated into four categories; worldviews in school practices, the neutrality of schools, visibility of individuals’ worldviews, and worldviews education. The principals’ role and responsibility in accepting actualisations were emphasised and there were differences in how principals considered and accepted the visibility of worldviews in schools.